Novel biomarkers for cardiovascular risk assessment: current status and future directions. (September 2015) - MacNamara, James; Eapen, Danny J; Quyyumi, Arshed; Sperling, Laurence
Cardiovascular disease (CVD) is the leading cause of mortality in the modern world. Traditional risk algorithms may miss up to 20% of CVD events. Therefore, there is a need for new cardiac biomarkers. Many fields of research are dedicated to improving cardiac risk prediction, including genomics, transcriptomics and proteomics. To date, even the most promising biomarkers have only demonstrated modest associations and predictive ability. Few have undergone randomized control trials. A number of biomarkers are targets to new therapies aimed to reduce cardiovascular risk. Currently, some of the most promising risk prediction has been demonstrated with panels of multiple biomarkers. This article reviews the current state and future of proteomic biomarkers and aggregate biomarker panels.